Cerebral Blood Volume after Birth Asphyxia - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1993)
Cerebral hemodynamics and oxygenation in 18 perinatally asphyxiated neonates were compared with 13 healthy controls using near-infrared spectroscopy (NIRS) at the Dept of Pediatrics, University Hospital of Leiden, The Netherlands.